The Impact of Federal Personnel Preparation Grants on Special Education Teacher Candidate Recruitment for Rural and Remote Alternative Teaching Pathways. (December 2019) - Jameson, J. Matt; Walker, Ryan M.; Farrell, Michael; Ryan, Joanna; Conradi, Lyndsey Aiono; McDonnell, John
This article describes rural and remote teacher training in low incidence (LI) disabilities through an alternative teaching pathway (ATP) and the efforts of one university's ATP program to address the ongoing critical special education teacher shortage in rural and remote school districts. The impact of the federal investment in recruiting/training teacher candidates in LI disabilities in rural and remote areas is described, and critical features of a distance education ATP programs in LI are discussed. Lessons learned over two decades of distance ATP delivery in LI are shared.